Peran Pendamping dalam Memberikan Pelayanan pada Anak Disabilitas di Yayasan Pendidikan Dwituna Harapan Baru - Nurul Fadillah Nasution; Tuti Atika (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
This  article  discusses  the  role  of  companions  in  providing  services  to  children  with  disabilities  at  the  Dwituna  Harapan  Baru  Education  Foundation.  The  existence  of  a  companion  for  children  with  special  needs  has  a  significant  meaning  for  the  process  of  protection  and  growth.  Social  assistance  is  a  strategy  that  greatly  determines  the  success  of  community  empowerment.  Mentoring  is  also  an  activity  that  means  coaching,  teaching,  directing  which  has  a  more  connotation  of  mastering,  controlling,  and  controlling.  Independence  in  children  is  needed  to  train  instincts  in  choosing  decisions  and  responsibilities.  For  children  with  special  needs,  moving  towards  independence  is  more  complicated  than  normal  children  because  of  the  limitations  they  have,  so  there  will  be  added  value  in  training  them.  The  process  towards  independence  in  these  children  requires  a  companion  role  in  every  process  of  child  development.  The  purpose  of  this  writing  is  as  a  result  of  the  author's  dedication  to  running  PKL  II  at  the  Dwituna  Harapan  Baru  Education  Foundation.  The  method  used  is  qualitative  research  with  data  collection  techniques  by  observation  and  interviews.  Secondary  data  sources  for  this  writing  are  journals  and  literature  that  can  support the analysis of the discussion.